Host Genetics at the Intersection of Autoimmunity and COVID-19: A Potential Key for Heterogeneous COVID-19 Severity - Karaderi, Tugce; Bareke, Halin; Kunter, Imge; Seytanoglu, Adil; Cagnan, Ilgin; Balci, Deniz; Barin, Burc; Hocaoglu, Mevhibe B.; Rahmioglu, Nilufer; Asilmaz, Esra; Taneri, Bahar (Frontiers in Immunology, 2020)
COVID-19 presentation is very heterogeneous across cases, and host factors are at the forefront for the variables affecting the disease manifestation. The immune system has emerged as a key determinant in shaping the outcome of SARS-CoV-2 infection. It is mainly the deleterious unconstrained immune response, rather than the virus itself, which leads to severe cases of COVID-19 and the associated mortality. Genetic susceptibility to dysregulated immune response is highly likely to be among the host factors for adverse disease outcome. Given that such genetic susceptibility has also been observed in autoimmune diseases (ADs), a number of critical questions remain unanswered; whether individuals with ADs have a significantly different risk for COVID-19-related complications compared to the general population, and whether studies on the genetics of ADs can shed some light on the host factors in COVID-19. In this perspective, we discuss the host genetic factors, which have been under investigation in association with COVID-19 severity. We touch upon the intricate link between autoimmunity and COVID-19 pathophysiology. We put forth a number of autoimmune susceptibility genes, which have the potential to be additional host genetic factors for modifying the severity of COVID-19 presentation. In summary, host genetics at the intersection of ADs and COVID-19 may serve as a source for understanding the heterogeneity of COVID-19 severity, and hence, potentially holds a key in achieving effective strategies in risk group identification, as well as effective treatments.